The Effect of the Picture and Picture Cooperative Learning Model on the Learning Outcomes of Fifth Grade Students in Science at SD Negeri 060834 Medan Petisah - Pasaribu, Yuni Omega Putri; Abi, Antonius Remigius; Tanjung, Darinda Sofia; Silaban, Patri Janson; Purba, Frikson Jony; Elango, Dinesh (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study aims to determine the effects of the picture and picture-learning model on the learning outcomes of fifth-grade students in IPAS at SD Negeri 060834 Medan Petisah in the 2024/2025 academic year. This study used a quantitative method. The research population consisted of all fifth-grade students at SD Negeri 060834 Medan Petisah, totaling 26 students. Sampling was conducted using a a total sampling technique, and the sample consisted of the fifth-grade class, totaling 26 students. The results of this study show that student learning outcomes using the picture and picture learning model are in the good category, with an average of 87.92 and a correlation coefficient of 0.776. This indicates that rcount (0.776) > rtable (0.404), so Ha is accepted. Therefore, the picture and picture learning model strongly influence student learning outcomes in the subject of IPAS (Science Education) on the material of Light and its Properties in grade V of SD Negeri 060834 Medan Petisah. This is evident from the t-test results, where tcount > ttable (6.036 > 2.056), so Ha is accepted. This indicates a significant positive effect of using the picture and picture-learning model on student learning outcomes in the IPAS subject for fifth-grade students at SD Negeri 060834 Medan Petisah in the 2024/2025 academic year.